2023
DOI: 10.1002/advs.202300180
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Remodeling of Microglial Riboflavin Metabolism Ameliorates Cognitive Impairment by Modulating Neuroinflammation

Abstract: Neuroinflammation, for which microglia are the predominant contributors, is a significant risk factor for cognitive dysfunction. Riboflavin (also known as vitamin B2) ameliorates cognitive impairment via anti‐oxidative stress and anti‐inflammation properties; however, the underlying mechanisms linking riboflavin metabolism and microglial function in cognitive impairment remain unclear. Here, it is demonstrated that riboflavin kinase (RFK), a critical enzyme in riboflavin metabolism, is specifically expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…It decreased CypD expression by 44.9%, inhibited Drp1 expression, and enhanced OPA1 expression to halt the mitochondrial dysfunction cascade. [226] Regulation of inflammation-related pathways (including upward and downward regulation) [227,228] can also enhance mitochondrial protection by cutting off the vicious circle between inflammation and other pathological phenomena such as oxidative stress. [229,230] Ac2-26, an Annexin 1(ANXA1) derived peptide, can prevent neutrophils from infiltrating and adhering by acting on the lipotoxin A4 receptor (ALXR/FPRL1) on the cell surface to repress inflammation.…”
Section: Inhibiting Mptp and Inflammatory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…It decreased CypD expression by 44.9%, inhibited Drp1 expression, and enhanced OPA1 expression to halt the mitochondrial dysfunction cascade. [226] Regulation of inflammation-related pathways (including upward and downward regulation) [227,228] can also enhance mitochondrial protection by cutting off the vicious circle between inflammation and other pathological phenomena such as oxidative stress. [229,230] Ac2-26, an Annexin 1(ANXA1) derived peptide, can prevent neutrophils from infiltrating and adhering by acting on the lipotoxin A4 receptor (ALXR/FPRL1) on the cell surface to repress inflammation.…”
Section: Inhibiting Mptp and Inflammatory Responsementioning
confidence: 99%
“…Cognitive Impairment MNPs@FMN [ 228] --106 -FMN Friedrich's ataxia Cur@SF NPs [ 276] --≈150 -Curcumin…”
Section: 𝛼-Mangostinmentioning
confidence: 99%
“…Reproduced from Ref. [124] with permission. (I) Mode of action and side effects (neuroinflammation) of lipid nanoparticles (LNP)‐Aβ, and the proposed therapeutic mechanisms of LNP‐R/Aβ for the treatment of Alzheimer's disease (AD).…”
Section: Nanomedicines For Alleviating Neuroinflammationmentioning
confidence: 99%
“…At present, only one report has suggested that the rapid capture of neutrophils by neutrophil extracellular traps at the inflammatory lesion site results in rapid degradation and the release of loaded drugs [181] . Biomimetic drug delivery systems based on macrophage [123] and microglia [124] membranes can help the drug reach the target lesion and become endocytosed by microglia, but it is still unclear how the drug is released. One recent study showed that a biomimetic carrier based on osteoclast membranes can circumvent lysosomes and achieve drug release through membrane fusion, and the absorbed drug can also be transported between cells via exosomes [182] .…”
Section: Nanomedicines For Alleviating Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation